Effect of teacher–student relationship on academic engagement: the mediating roles of perceived social support and academic pressure - Liu, Xiangliang (Frontiers in Psychology, 2024)
Although previous research has established that a strong teacher–student relationship can enhance students’ academic engagement, the mechanisms underlying this effect remain less explored. Therefore, this study examined the mediating roles of perceived social support and academic pressure in the association between teacher–student relationship and academic engagement. A survey involving 1,058 Chinese university students was conducted, with teacher–student relationship, perceived social support, academic pressure, and academic engagement being the evaluated factors. The results of structural equation modeling revealed that (a) teacher–student relationship directly and positively associated academic engagement, (b) teacher–student relationship indirectly and positively associated academic engagement through perceived social support, and (c) teacher–student relationship indirectly and positively associated academic engagement through both perceived social support and academic pressure. These results indicate that perceived social support and academic pressure are the primary factors mediating the effect of teacher–student relationship on academic engagement among university students.